These who rent themselves for movies/ of the most brutal raw pornography, Jorge de Sena and the works - Cruz, Beatriz Helena Souza da (Revista de Letras, 2020)
We observe the presence of work in the Seniana work, in different ways. Thus, recalling that work is as broad a theme as the meanings of the word, we intend to observe how it is represented in the work of Jorge de Sena, from the location of a group of poems in which there are, among other issues, different situations of workers inserted in Capitalism, notably set in the twentieth century, as well as examples of the relationships and implications of work in human life. For this, the writings of the Sena, scholars of different areas such as Karl Marx and Herbert Marcuse, among others, constitute the theoretical and critical basis of this work. We will bring the criticism of the poet to the exploitation implemented by this system, rescuing the place of work in the construction of man while being endowed with intelligence and producer of culture, which changes while transforming nature, according to Marx.